In-vivo and in-vitro nutrients digestibility of raw and processed Hibiscus sabdariffa (Roselle) seed meal fed to the Nile Tilapia (Oreochromis niloticus) - Yunusa, A; Oyegbile, B (Nigerian Journal of Animal Science, 2023)
This study was conducted to determine the in-vivo and in-vitro apparent digestibility coefficient of nutrients in raw and processed Hibiscus sabdariffa (Roselle) seed meals. In the in-vivo digestibility, Acid Insoluble Ash (AIA) was used as an indicator. Five experimental diets were formulated using raw roselle, (RR) soaked roselle, (SR) boiled roselle,(BR) sprouted roselle (SR) and fermented roselle (FR) to feed Oreochromis niloticus fingerlings inside fifteen plastic aquaria of 60cm x 50cm x 30cm dimension with 120L water holding capacity to determine the effect of raw and processed roselle on the digestibility of the oil seed. Ten fingerlings of O. niloticus (initial total weight 0.60kg) were stocked in each aquarium with three replicates. The results obtained revealed that the apparent digestibility coefficient (ADC) for protein were highest in fermented roselle (88.20%) followed by boiled roselle (86.40%), sprouted roselle (85.74%), soaked roselle was 81.43% and the raw roselle was the least with 79.57%. The ADC for Crude Lipid was 57.90%, 50.17%, 57.80%, 50.54% and 49.75% for fermented roselle, sprouted roselle, boiled roselle, soaked roselle and raw roselle respectively. The results for the digestibility coefficient of roselle seed meals analyzed in-vitro using casein as the control showed that the ADC for protein were also highest in fermented, roselle 90.50%, followed by boiled roselle (85.00%), soaked roselle (75.00) and lastly raw roselle (70.00%). There were significant differences (p < 0.05) in all the processing methods. In both the in-vivo and in-vitro digestibility, fermented roselle presented the highest digestibility of 88.20% and 90.50% respectively. These values compares favorably with other oil seed meals and legumes used in aquafeeds.